1999
DOI: 10.1021/ac981208u
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Tissue Site-Selective Lanthanide Chelate, Tb-PCTMB for Enhanced Imaging of Cancer

Abstract: In-vivo and in-vitro investigations indicate that a newly developed polyazamacrocyclic chelate of Tb(III) has superior properties for use as an abnormal tissue marker. In addition to tissue selectivity, this molecule is unique because of its low toxicity, attractive fluorescent properties, rapid pharmokinetics, and relatively high water solubility. The complex Tb-3,6,9-tris(methylene phosphonic acid n-butyl ester)-3,6,9,15-tetraazabicyclo[9.3.1]-pentadeca-1(15),11,13 -triene (Tb-PCTMB) has also been shown to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…8). The luminescent Tb(III) complexes possess high quantum yields 72 and supporting studies reported the use of 153 Sm complexes which showed localisation in bone tissue of rats. 73 It is noteworthy that related coordination chemistry with 90 Y has been reported with PCTMB (Fig.…”
Section: Macrocyclic Ligand Derivativessupporting
confidence: 58%
“…8). The luminescent Tb(III) complexes possess high quantum yields 72 and supporting studies reported the use of 153 Sm complexes which showed localisation in bone tissue of rats. 73 It is noteworthy that related coordination chemistry with 90 Y has been reported with PCTMB (Fig.…”
Section: Macrocyclic Ligand Derivativessupporting
confidence: 58%
“…Keywords: helical structures · heterometallic complexes · imaging agents · lanthanides · luminescence dine-based cryptands, [16] cyclen derivatives containing coordinating and sensitizing groups, [17] aza-macrocycles incorporating a pyridine, bipyridine or terpyridine unit [18,19] and b-diketonates [20] ), which often have in common the simultaneous use of carboxylate (or amide) and amine coordinating groups.…”
Section: IIImentioning
confidence: 99%
“…[25] Tb III -based chelates have also proved useful, as exemplified by a lipid-conjugated chelate that functions as a membrane-staining agent in morphological studies of Swiss albino mouse 3T3 cultured cells, [22] or by Bornhops high brightness macrocyclic labels for in vitro and in vivo analysis of abnormal tissues. [18,26,27] More recently, Parker and co-workers have designed Eu III complexes that specifically stain the nucleoli of several cell lines (CHO, COS, NIH 3T3, HeLa, and HDF). [15,[28][29][30] Most lanthanide ions are also paramagnetic and possess an anisotropic susceptibility tensor that makes them useful for the structural investigation of axial complexes [31] or proteins [32] by NMR spectroscopy, while Gd III has emerged as a universal contrast agent for 3D imaging of biological structures (MRI).…”
Section: IIImentioning
confidence: 99%
“…14,21-24 Several research groups are examining the use of contrast agents for breast cancer detection. [24][25][26][27][28] Others have performed animal studies using window chambers to provide direct optical access to study the microenvironment of a tumor. 29,30 A number of ex vivo studies of the optical properties of normal and diseased breast tissue have also been performed.…”
Section: Introductionmentioning
confidence: 99%